Pengelolaan dan Inventarisir Sarana dan Prasarana di Lingkungan Perpustakaan Daerah Studi Minat Baca Anak, Pojok Baca dan Literasi Talling Story dalam Menumbuhkan Kembangkan Sensori Motorik Pada Anak - Muhammad Ibnu Faruk Fauzi; Kamaria Kamaria (Politeknik Kampar, 2023)
This study aims to investigate the management and inventory of facilities and infrastructure in the library area of ??the study area for children's reading interest, reading corners, and storytelling literacy and their impact on sensory-motor development in children. This study uses a descriptive approach by gathering information from available sources. The research findings indicate that there are various well-managed facilities and infrastructure in the library, such as a collection of children's books, interactive games, and comfort facilities that support motor sensory. Effective management and inventory allows children to engage in reading activities and games that stimulate their sensory-motor development. The implications of this study show the importance of good management in creating a library environment that facilitates sensory-motor development in children. This research contributes to our understanding of the role of regional libraries for children's reading interest studies, reading corners, and storytelling literacy in enriching children's sensory-motor experiences. The results of this study can be used as a basis for further improvement in the management of facilities and infrastructure in the library environment which focuses on the sensory-motor development of children.